Determining the strength of a frame in a railroad open wagon with slings in its structure to improve its operational energy efficiency - Lovska, Alyona; Stanovska, Iraida; Pelypenko, Yevhen; Barsukova, Hanna; Yurchenko, Oleksandr (Technology center PC, 2025)
This study's object is the processes related to load acceptance and redistribution within the frame of a railroad open wagon with slings in the structure under operational loads. The task addressed in the study is to reduce the loading on the open wagon frame during operation by installing slings in its cantilever parts. To substantiate this technological advancement, the strength of an open wagon frame was calculated under the basic load schemes in operation. The dynamic loads acting on the open wagon frame were determined by mathematical modeling. The strength calculations performed showed that the maximum stresses in the railroad open wagon frame occur under the first design mode. However, these stresses are 6% lower than those that occur in a typical frame structure. In addition, within the framework of the study, the strength of a railroad open wagon frame was calculated while transported by railroad ferry. The calculation results showed that the strength of the open wagon frame is ensured. The estimated stresses are 4% lower than those in the typical structure of an open wagon frame. A feature of the proposed technological advancement is that its implementation is feasible at the stage of wagon modernization, rather than only during the manufacture of new structures. The area of practical use of the results is railroad transport. A condition for the practical implementation of this study's results is to link the sling to the areas of arranging the front and rear stops of auto couplers. The results of the research will contribute to improving the strength of the supporting structures in open wagons during operation and reducing the costs of their maintenance. The findings could also contribute to the design of freight wagons with improved technical and economic indicators.
Keywords: railroad transport; railroad open wagon; open wagon frame; frame improvement; frame strength; structural energy efficiency